Promoting Harmony Through Education: Girls Students Perspective from Northern Punjab - Mehlah Jabeen; Naveen Amber; Muhammad Moin (JELM, 2023)
In every society peace and harmony has been the eventual need since the time immemorial. Students naturally engross the spirit of harmony from their environment and develop their perceptions accordingly. Majority of the girls became victims of violence, hatred, ignorance, anger, terrorism, despair, however, peace education is the only way for them to get rid from this gloomy condition. So, on urgent basis peace should instill in individuals mind mainly the students. Present study aimed to examine the perceptions of girls in public secondary schools of Northern Punjab regarding promoting peace through education. Keeping in view the objectives of the study, the quantitative research design was used to execute the study. The participants of the study were 200 public secondary school girls from two districts of Northern Punjab, namely, Mandi Bahauddin and Sargodha. Data were collected through questionnaire in the affective domain ‘Schema of Peace Education’ formulated by Castro and Galace (2010). Analysis of the data revealed that the girls’ students sustain peaceful attitude as a whole. Most of the students showed their positive attitude on self-respect, respect for others, compassion and justice. Some of the respondents disagreed with global concern, social responsibility and positive vision. It was recommended that peace education with activities should include as a subject in the formal curriculum of schools to highlight its utmost importance in the society.